Intensive luminescence from a thick, indium-rich In0.7Ga0.3N film. (28th May 2019) - Sheng, Bowen; Bertram, Frank; Zheng, Xiantong; Wang, Ping; Schmidt, Gordon; Veit, Peter; Bläsing, Jürgen; Chen, Zhaoying; Strittmatter, André; Christen, Jürgen; Shen, Bo; Wang, Xinqiang
Abstract: An In0.7 Ga0.3 N layer with a thickness of 300 nm deposited on GaN/sapphire template by molecular beam epitaxy has been investigated by highly spatially resolved cathodoluminescence (CL). High crystal film quality without phase separation has been achieved. The InGaN layer shows intense emission in the IR spectral region. The lateral as well as the vertical luminescence distribution is used to probe the In composition ([In]) homogeneity: the thick InGaN film exhibits laterally a rather homogeneous emission intensity at 1.04 eV (∼1185 nm) with a FWHM of only 63 meV. Carrier localization into regions of enhanced In concentration originating from compositional fluctuations is revealed. The evolution of emission in growth direction has been explored by a cross-sectional CL linescan showing a slight spectral redshift from the bottom to the surface of the InGaN film corresponding to an increase of [In] of only 0.5% within the layer thickness of 300 nm.